Kajian Fonologi Bahasa Arab dalam Perspektif Psikolinguistik dan Pemrosesan Bahasa - Adiebah, Meilina Husna; Choliliyah, Isro'atul; Mahliatussikah, Hanik (Fakultas Teknik Universitas Negeri Makassar, 2025)
This article aims to explore the phonology of the Arabic language, its relationship with psycholinguistics, and how the processing of Arabic phonemes occurs in the human brain. Further, it delves into the influence of the phonological system on both language comprehension and production, the challenges faced by non-native speakers in learning Arabic, and effective pedagogical approaches for teaching it. This study incorporates both theoretical frameworks and empirical research to examine the intricate relationship between phonological aspects, cognitive processes, and Arabic language acquisition. The article underscores the significance of mastering phonology as a foundational skill for effective communication in Arabic, both spoken and written and highlights the importance of integrating phonetic-based strategies into language learning. This comprehensive approach is crucial for developing a systematic, logical, and contextually relevant understanding of Arabic in psycholinguistic terms.